The socioeconomic determinants of urban poverty in Saudi Arabia - Miriam Al Lily; Hermann Waibel (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2021)
This paper presents results from one of the first independent socioeconomic household surveys to study urban poverty among Saudi nationals. This survey was administered to 496 Saudi households in Dammam in 2019. Poverty is conceptualised as relative poverty, which is based on the country's inflation adjusted national poverty line of 6 per person per day. The methodology is based on the Foster-Greer-Thorbecke (FGT) poverty index, which is used to analyse the socioeconomic determinants of the prevalence, intensity, and severity of poverty. The results indicate that education and unemployment are crucial determinants of poverty outcomes. In addition, large family sizes combined with the tradition of having a single breadwinner also pushes households into poverty. Female-headed households are particularly vulnerable. Furthermore, social capital positively impacts the welfare of households, whereas being of African descent has a negative influence. However, health, personal attitudes, and being of Bedouin origin are not significant variables in the model. The social welfare system is able to mitigate some of the disadvantages, but not all. Overall, approximately one third of poor households are being lifted out of poverty by social welfare payments.
Keywords: O12; I32; 330; Arab World; Social Exclusion; Urban Poverty; Poverty Determinants; Poverty Gap